Plasma Concentrations of Fibroblast Growth Factors 19 and 21 in Patients with Anorexia Nervosa - DOSTALOVA, Ivana; KAVALKOVA, Petra; HALUZIKOVA, Denisa; LACINOVA, Zdena; MRAZ, Milos; PAPEGOVA, Hana; HALUZIK, Martin (The journal of clinical endocrinology and metabolism, 2008)
Context: Fibroblast growth factor 19 (FGF19) and FGF21 are novel metabolic regulators that improve insulin sensitivity and decrease adiposity in mice. However, little is known about the nutritional regulation of these factors in humans. Objective: The objective of this study was to measure plasma FGF19 and FGF21 levels in patients with anorexia nervosa (AN) and to explore its relationship with anthropometric and endocrine parameters. Design: This was a single-center cross-sectional study. Setting: The study was performed in a university hospital. Patients: Seventeen untreated women with a restrictive type of AN and 17 healthy women (control group) were included. Main Outcome Measures: Fasting plasma FGF19 and FGF21, serum insulin, leptin, soluble leptin receptor, adiponectin, resistin, and C-reactive protein were the main outcome measures. Results: Plasma FGF19 levels did not significantly differ between the groups studied, whereas plasma FGF21 levels were significantly reduced in AN relative to the control group. Plasma FGF21 positively correlated with body mass index and serum leptin and insulin and was inversely related to serum adiponectin in both groups. In contrast, plasma FGF19 was not related to any of parameters studied. Partial realimentation significantly reduced plasma FGF21 levels in AN. Conclusion: Circulating levels of FGF21 but not FGF19 are strongly related to body weight and serum levels of leptin, adiponectin, and insulin in both anorectic and normal-weight women. We suggest that reduced plasma FGF21 levels could be involved in the pathophysiology of AN or in a complex adaptive response to this disease.